A Comparison of Fat Graft Processing Techniques: Outcomes in 1, 158 Procedures in Prosthetic Breast Reconstructions. Issue 11 (November 2019) - Chiu, Wen-Kuan; Fracol, Megan; Feld, Lauren N.; Qiu, Cecil S.; Kim, John Y.S.
Abstract : Background: As fat grafting in breast reconstruction evolves, questions of technique and outcomes persist. We compared 2 common fat processing techniques—decantation (DEC) versus closed wash and filtration (CWF)—with regard to outcomes and efficacy. Methods: Chart review of a single surgeon experience with breast fat grafting was performed. Data extracted included demographics, technique, complications, graft volume, and revision rates. Secondarily, the timeline of complication profiles was analyzed. Lastly, subgroup analysis of radiated versus nonradiated breast outcomes was performed. Results: One thousand one hundred fifty-eight fat grafting procedures were performed on 775 breasts (654 DEC, 504 CWF). Time-to-event analysis for all complications showed no difference between groups. Independent risk factors for fat necrosis included DEC technique, body mass index >30 kg/m 2, and fat injection >75 mL. The majority of cases of fat necrosis, cyst/nodule formation, ultrasounds, and biopsies occurred more than 6 months after grafting. Average graft volume was lower in DEC compared with CWF breasts (50.6 versus 105.0 mL, P < 0.01), and more DEC breasts required repeat fat grafting procedures (39.9% versus 29.6%, P < 0.01). Radiated breasts received larger fat graft volume (89.9 versus 72.4 mL, P < 0.01) and required more fat graft procedures (average 1.62 versus 1.47, P < 0.01). Conclusions: This study represents the largest series of breast reconstruction fat grafting to date. DEC harvest technique may be a risk factor for fat necrosis, which results in less fat injection and greater need for repeat procedures. Similarly, radiated breasts require larger graft volume and more repeat procedures.